2014
DOI: 10.5935/medicalexpress.2014.05.04
|View full text |Cite
|
Sign up to set email alerts
|

Yoga Relaxation (savasana) decreases cardiac sympathovagal balance in hypertensive patients

Abstract: OBJECTIVE: Although relaxation is recommended as complementary therapy for hypertension, its postintervention cardiovascular autonomic effects are unclear. The objective of this research was to investigate the effects of savasana relaxation on cardiovascular autonomic modulation in hypertensive patients. METHODS: This randomized controlled trial was performed at the Hemodynamic Laboratory of the Physical Education School of the University of Sã o Paulo/Brazil. Sixteen hypertensive (6-women) and 14 normotensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…8 The literature indicates that yoga-based lifestyle intervention favorably modifies various cardiovascular and metabolic parameters. [9][10][11] Various limbs of yoga, including asana, pranayama, and meditation, improve the sympathovagal response, which is evident from the increase in HRV and restoration of baroreflex sensitivity. 6,12 Accumulating evidence suggests that yoga might have a favorable effect on cardiac autonomic function.…”
Section: Introductionmentioning
confidence: 99%
“…8 The literature indicates that yoga-based lifestyle intervention favorably modifies various cardiovascular and metabolic parameters. [9][10][11] Various limbs of yoga, including asana, pranayama, and meditation, improve the sympathovagal response, which is evident from the increase in HRV and restoration of baroreflex sensitivity. 6,12 Accumulating evidence suggests that yoga might have a favorable effect on cardiac autonomic function.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Another study of 60 healthy individuals showed that a 12-week alternate nostril breathing exercise program showed a significant decrease in the mean SBP of the participants. [27] The results of this study showed that the patients who participated in the silent sitting session showed a decrease of approximately 3 and 5 mmHg in the SBP and DBP, respectively, whereas the patients who performed the alternate nostril breathing exercise showed a decrease of about 4 mmHg in both SBP and DBP measured at the end of the second week ( Table 3). Results of intergroup evaluation of the decrease in BP showed a significant decrease in the SBP of patients who performed the breathing exercises, which is consistent with the findings reported previous (p<0.05) ( Table 3).…”
Section: Discussionmentioning
confidence: 68%
“…and increased HFn.u. [ 22 35 36 40 ] while two different studies of TM in advanced meditators reported increased HF power during periods of meditation compared to baseline eyes closed[ 37 ] and during periods of transcendental experience compared to other experiences during meditation. [ 38 ] The one study examining HRV during meditation ( dhyana ), focused thinking ( dharana ), nonmeditative thinking ( ekagrata ), and random thinking ( cancatla ) reported reduced LFn.u.…”
Section: Resultsmentioning
confidence: 99%
“…after yoga relaxation compared to supine rest. [ 40 ] Furthermore, one study that compared HRV at baseline with HRV after yoga relaxation reported no change in HRV. [ 39 ]…”
Section: Resultsmentioning
confidence: 99%